2005
DOI: 10.4049/jimmunol.175.4.2286
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Myelin Oligodendrocyte Glycoprotein-Induced Experimental Autoimmune Encephalomyelitis by Death Receptor 6-Deficient Mice

Abstract: Genetic disruption of death receptor 6 (DR6) results in enhanced CD4+ T cell expansion, Th2 differentiation, and humoral responses after stimulation. However, the in vivo consequences of DR6 targeting (DR6−/−) during the initiation and progression of inflammatory autoimmune disease are unclear. Using a myelin oligodendrocyte glycoprotein (MOG35–55)-induced model of experimental autoimmune encephalomyelitis, DR6−/− mice were found to be highly resistant to both the onset and the progression of CNS disease compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…DR6, a member of the death domain-containing TNFR superfamily member is highly expressed in lymphoid tissues and its expression is tightly regulated upon lymphocyte activation [7]. Using DR6-deficient mice, we have previously shown that DR6 plays a critical regulatory role for development of adaptive immune response [7][8][9]. Lack of DR6 resulted in enhanced proliferative response of splenic CD4 + T cells to T cell receptor activation [7].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…DR6, a member of the death domain-containing TNFR superfamily member is highly expressed in lymphoid tissues and its expression is tightly regulated upon lymphocyte activation [7]. Using DR6-deficient mice, we have previously shown that DR6 plays a critical regulatory role for development of adaptive immune response [7][8][9]. Lack of DR6 resulted in enhanced proliferative response of splenic CD4 + T cells to T cell receptor activation [7].…”
Section: Introductionmentioning
confidence: 95%
“…Immunization of DR6 −/− mice with protein antigens such as Keyhole Limpet Hemocyanin in complete Freund's adjuvant (CFA) leads to enhanced Th2 cytokine production after ex vivo antigen challenge [7]. Furthermore, DR6 −/− mice immunized with a self-antigenic peptide derived from myelin oligodendrocyte glycoprotein in CFA were largely resistant to the development of experimental autoimmune encephalomyelitis (EAE), a largely Th1-driven inflammatory autoimmune disease of the central nervous system [9]. DR6 −/− mice displayed increased Th2 cytokine production after ex vivo antigen challenge during EAE progression, and associated with severely impaired accu- mulation of inflammatory T cells in the CNS [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic plasticity in the spinal cord may explain, at least in part, the rapid sensorimotor recovery of the animals soon after tetraplegia (3,5). In view of the importance of a better understanding of MS as well as its experimental models, major advances in understanding how cellular and humoral immune responses contribute to the pathogenesis of these diseases have been made in recent years (8)(9)(10)(11)(12). Thus, targeting key elements of the immunological cascade that culminate in neural and glial tissue damage may offer a number of advantages over currently available treatment strategies (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…DR6 regulates CD4 + T cell proliferation and Th cell differentiation and is also expressed on resting B cells but is downregulated upon activation of the latter (Liu et al, 2001;Schmidt et al, 2002). Studies on DR6-deficient (DR6 2/2 ) mice have shown the crucial regulatory role played by this receptor in the development of the adaptive immune response (Liu et al, 2001;Schmidt et al, 2005). High expression of DR6 in human cancer cell lines and tumor samples seems to be regulated by the TNF-a-induced NF-kB activation pathway, the activity of which correlates with a constitutive high basal level of NF-kB activation (Benschop et al, 2009).…”
Section: Introductionmentioning
confidence: 99%